Prevalence and determinants of obesity in students with intellectual disability in Jakarta (Medical Journal of Indonesia, 2014)
Background: The group of people with health problems and has not received a proper attention is those with intellectual disability (ID) with obesity. The study aimed to get the prevalence of obesity in ID students in Jakarta, and to assess its relationship with age, sex, and parental education. Methods: This is a cross sectional study. The subjects are students of special schools for the disabled type C/C1 in DKI Jakarta area aged 10-30 year old. The definition of obesity for subjects aged 10-20 year old utilized the ≥ 95th percentile of BMI according to the appropriate sex and age group. Meanwhile, the definition of obesity for those aged 21-30 year old is the BMI according to WHO for Asia Pacific, which is ≥ 25.0. The analysis to test the determinant factors was performed using chi-square test. Results: The prevalence of obesity for ID students of special schools type C/C1 in DKI Jakarta area is 282 people or 16% of the total of 1,760 subjects, and there are statistically significant difference between the prevalence of obesity among the age groups (p < 0.001), sex (p = 0.039) and parental education (p < 0.006 for father’s education and p < 0.001 for mother’s education level). Conclusion: The prevalence of obesity among ID students in special schools for the disabled type C/C1 in Jakarta is 16%, with the age, sex, and parental education level as determinant factors associated with obesity.